Highly cross-linked Cu/a-Si core–shell nanowires for ultra-long cycle life and high rate lithium batteries. Issue 5 (17th November 2015) - Wang, Hongxiang; Song, Hucheng; Lin, Zixia; Jiang, Xiaofan; Zhang, Xiaowei; YU, Linwei; XU, Jun; Pan, Lijia; Wang, Junzhuan; Zheng, Mingbo; Shi, Yi; Chen, Kunji
Abstract : An optimal highly cross-linked composite Cu/a-Si core–shell structure design has enabled a long cycle lifetime and high rate performance for silicon-loaded lithium ion batteries. Abstract : Seeking long cycle lifetime and high rate performance are still challenging aspects to promote the application of silicon-loaded lithium ion batteries (LIBs), where optimal structural and compositional design are critical to maximize a synergistic effect in composite core–shell nanowire anode structures. We here propose and demonstrate a high quality conformal coating of an amorphous Si (a-Si) thin film over a matrix of highly cross-linked CuO nanowires (NWs). The conformal a-Si coating can serve as both a high capacity storage medium and a high quality binder that joins crossing CuO NWs into a continuous network. And the CuO NWs can be reduced into highly conductive Cu cores in low temperature H2 annealing. In this way, we have demonstrated an excellent cycling stability that lasts more than 700 (or 1000) charge/discharge cycles at a current density of 3.6 A g −1 (or 1 A g −1 ), with a high capacity retention rate of 80%. Remarkably, these Cu/a-Si core–shell anode structures can survive an extremely high charging current density of 64 A g −1 for 25 runs, and then recover 75% initial capacity when returning to 1 A g −1 . We also present the first and straightforward experimental proof that these robust highly-cross-linked core–shell networks can preserve the structural integrity even after 1000 runs of cycling. All these results indicate a new and convenient strategy towards a high performance Si-loaded battery application.